(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
A total of eight compounds including four starting materials and four indolium chloride derivatives were tested against Gram positive and Gram negative bacterial and fungal strains. Among them, N-acetyl-2- acetylindoliumchloride (8) exhibited significant antimicrobial activity at a concentration of 200 μg/disc, while the Nacetyl- 2-benzoylindoliumchloride (9) showed moderate activity at 400 μg/disc. At the same time, N-acetyl-2- anisoylindoliumchloride (10) and N-acetyl-2-tolylindoliumchloride (11) demonstrated weak antimicrobial activity. Dhaka Univ. J. Pharm. Sci. 19(2): 133-137, 2020 (December)